Emotional and sensory dysregulation as a possible missing link in attention deficit hyperactivity disorder: A review - Grossman, Anna; Avital, Avi (Frontiers in Behavioral Neuroscience, 2023)
Attention Deficit Hyperactivity Disorder (ADHD) is a common developmental disorder affecting 5-7% of adults and children. We surveyed the literature to examine ADHD through three pillars: developmental characteristics, symptomatology, and treatment strategies. Firstly, in terms of develeopmental characterstics, early life stress may increase the risk of developing ADHD symptoms according to animal models’ research. Secondly, the current core symptoms of ADHD are comprised of inattention, hyperactivity, and impulsivity. However, the up-to-date literature indicates individuals with ADHD experience emotional and sensory dysregulation as well, which early-life stress may also increase the risk of. Finally, we discuss the therapeutic benefits of methylphenidate on both the current core ADHD symptoms and the sensory and emotional dysregulation found in those with ADHD. In summation, we surveyed the recent literature to analyze (i) the potential role of early-life stress in ADHD development, (ii) the involvement of emotional and sensory dysregulation in ADHD symptomatology and finally, (iii) the therapeutic intervention with methylphenidate, aiming to reduce the potential effect of early life stress in ADHD, and mainly emotional and sensory dysregulation. The apparent but currently less recognized additional symptoms of emotional and sensory dysregulation in ADHD call for further investigation of these possible causes and thus increasing treatments efficacy in individuals with ADHD.